Interaction between the antimicrobial peptide Aurein 1.2 dimer and mannans - Lorenzon, Esteban N. [UNESP]; Piccoli, Julia P. [UNESP]; Cilli, Eduardo M. [UNESP] (Springer, 2014)
We have previously described the structure and the ability of a dimeric analog of the antimicrobial peptide Aurein 1.2 to aggregate Candida albicans. In this study, circular dichroism and fluorescence spectroscopy data showed that this aggregation is related to the interaction between the peptide and mannans, the main component of yeast cell wall. In this context, we propose a model in which dimers interact with the polysaccharide leading to cells aggregation.
Keywords: Aurein 1.2; Dimerization; Candida albicans; Aggregation; Mannans